THE UNHEARD VOICES IN PSALMS 90, 91, AND 92 - N.L. deClaissé-Walford (Acta Theologica)
A close reading of Psalms 90, 91, and 92, along with an understanding of the “storyline” of the Psalter as a whole, reveals “voices” within the three psalms that go largely unnoticed in translations of the Masoretic Text. This article outlines the placement of Psalms 90, 91, and 92 in the overall “shape” of the book of Psalms, examines their interconnectedness, discusses in detail various key Hebrew words and phrases, and demonstrates that we may hear within the three psalms the often neglected voices of Israelite women who were key actors in the Exodus from Egypt, the Babylonian Exile, and the Postexilic community.